Samopublikowanie prac naukowych i literatury pięknej - Frączek-Biłat , Ewa (Załącznik Kulturoznawczy, 2023)
The article draws attention to the accurate and inaccurate using of the term ‘self-publishing’. It shows also the different circumstances that affect the growing popularity of this phenomenon. Essentially the article focuses on the specific difference between the situation in the academic publishing market and the situation faced by writers and publishers of the fiction.